The Influence of Advertising Appeals on Consumers' Willingness to Participate in Sustainable Tourism Consumption. (29th October 2020) - Zhang, Hui; Mou, Yupeng; Wang, Tao; Hu, Jia
Abstract : Sustainable consumption has attracted much attention from the tourism industry. However, from the perspective of academic research, the psychological mechanism of collaborative consumption has not been thoroughly understood as the main form of sustainable consumption. This study explores the impact of advertising appeals on consumers' willingness to participate in collaborative consumption. Through two psychological experiments, it is believed that, relative to the rational appeal, the emotional appeal will positively affect consumers' participation willingness to collaborative consumption, and psychological ownership mediates this relationship. Furthermore, the form of information presentation moderates the influence of advertising appeals on psychological ownership.